BUILDING INTERNAL INNOVATION CAPACITY IN LARGE ENTERPRISES: A STRATEGIC IMPERATIVE - Alexandra POPESCU-ZORICA (Business Excellence and Management)
This paper explores the necessity for large enterprises to develop robust internal innovation capabilities as a strategic imperative for sustaining long-term competitiveness. While 83% of global companies prioritize innovation, only 3% demonstrate high innovation readiness, highlighting a gap between ambition and execution. The study employs a literature review and case study analysis to examine the structural and cultural barriers that hinder corporate innovation, including risk aversion, hierarchical decision-making, and a focus on operational efficiency over exploration. The research further evaluates leading innovation governance models, including Deschamps & Nelson’s governance structures and Brouwer’s hierarchical, market-driven, and hybrid models, as well as practical innovation frameworks such as the Ambidextrous Organization Model and Doblin’s Ten Types of Innovation. The findings suggest that companies must move beyond incremental improvements and acquisitions by implementing adaptive governance structures, cross-functional collaboration, and long-term strategic foresight. The paper identifies a set of best practices for developing innovation capacity, including the integration of intrapreneurship programs, AI-driven innovation, open innovation partnerships, and agile methodologies. The research concludes that organizations achieving a balance between governance structure, innovation frameworks, and strategic adaptability outperform competitors in growth and resilience. Recommendations include establishing leadership commitment, aligning innovation efforts with corporate strategy, and fostering a culture of experimentation to drive long-term business success.